Efektivitas Pembelajaran Etnomatematika “Permainan Engklek” Terhadap Pemahaman Konsep Geometri Siswa Sekolah Dasar - Dini Wahyu Mulyasari; Abdussakir Abdussakir; Dewi Rosikhoh (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2021)
Mathematics learning in elementary schools frequently encountered obstacles in material delivery. It was due to the abstract concepts of mathematics and the character of students who entered the concrete operational phase. Ethnomathematics learning could become an effort to overcome those obstacles. The purpose of this study was to determined the effectiveness of learning ethnomathematics